Implementation of Digital-Based Inheritance Distribution in Islamic Law: A Maqaṣid al-Syari'ah Perspective - Marbujang Marbujang; Putrado Herlianysah; Suweknyo Suweknyo; Handika Utama Putra; Yerry Anro Foza (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
The study seeks to evaluate the feasibility of implementing a digital inheritance distribution system while maintaining the essential principles of fiqh al-mawārīts and the overarching aims of maqāṣid al-syarī‘ah. Using a qualitative–descriptive approach grounded in library research, the analysis draws upon classical and contemporary Islamic legal sources, the Compilation of Islamic Law (KHI), and the Electronic Information and Transactions Law (UU ITE). The findings demonstrate that digital tools can significantly improve the efficiency, precision, and transparency of determining the rightful shares of heirs. Sharia-oriented algorithms not only ensure accuracy in calculations but also reinforce procedural integrity and legal accountability. Viewed through the lens of maqāṣid al-syarī‘ah, digitalization supports the preservation of wealth (ḥifẓ al-māl) and the protection of intellect (ḥifẓ al-‘aql) by minimizing human error and reducing opportunities for data manipulation. The study further reveals that the UU ITE’s acknowledgment of digital documents as legitimate evidence provides a firm legal basis for their implementation within religious judicial institutions. On the social front, the adoption of digital systems enhances public confidence in the fairness of Islamic legal processes and reduces the likelihood of family disputes. Ultimately, this research makes meaningful contributions to the development of Islamic legal technology and highlights potential future integrations, such as AI and blockchain, to support advanced inheritance management.